Efficient Interfacial Charge Transfer Based on 2D/2D Heterojunctions of Fe-C3N4/Ti3C2 for Improving the Photocatalytic Degradation of Antibiotics - Huo, Zhaohui; Liao, Yanmin; He, Yongyi; Zhang, Yifan; Liao, Xiaolin; Zhang, Qitong; Wu, Haojie; Shi, Junjie; Wen, Genglong; Su, Haixia; Yao, Suyang (Frontiers in Chemistry, 2022)
Graphitic carbon nitride (g-C3N4) has shown to be a promising photocatalyst that, however, suffers from strong charge recombination and poor conductivity, while MXenes have shown to be perfect cocatalysts for the photocatalytic process but show poor stability. In this study, we successfully constructed 2D/2D heterojunctions of Fe-C3N4/Ti3C2 for the photocatalytic degradation of antibiotics. In this study, multilayer Ti3C2 was obtained by etching Ti3AlC2, and then Fe-C3N4/Ti3C2 photocatalyst was prepared by the one-pot microwave method and high-temperature calcination method. The synthesized samples were characterized by XRD, SEM, TEM, XPS, TGA, BET, DRS, PL, and other means. The photocatalytic degradation of tetracycline hydrochloride by Fe-C3N4/Ti3C2 was in accordance with the first-order reaction kinetics model, and the apparent rate constant k was 2.83, 2.06, and 1.77 times that of g-C3N4, Fe-C3N4, and g-C3N4/Ti3C2, respectively. Through the mechanism study, it was shown that the most active species in the reaction system was • O2−, while h+ and •OH had a relatively lower effect on the degradation system.